Minerales espaciales: cosas de nadie en beneficio de todos - Marinho Amorim, Hellen; Reis Rochael, Carlos Henrique (Pontificia Universidad Católica del Perú. Fondo Editorial, 2019)
The exploitation of terrestrial mineral resources has been a source of economic benefits, environmental damage and human costs. New technologies, however, have been promoting space mining with the potential of synchronizing the benefits of this economic activity and reducing social and environmental damages. In this perspective, the present study examines two legal implications of this technological innovation: the legal nature and the ownership of natural space resources. With the objective of recognizing the most plausible legal subject, according to legal, logical and ethical criteria, in order to obtain title to the right of ownership of space ores and to propose the most appropriate treatment for their profits, the approach adopted aims to link land and space mining based on the perspective of renewed continuity. In order to reach this theoretical proposition, were previously analyzed the human and environmental impacts of terrestrial mining; the feasibility of using and exploiting space ores, as well as the advantages and disadvantages of space mining; and both the political and normative positions —international and local— and the academic-doctrinal positions —negationists, expansionists and analogists—about this property right. It is concluded that space ores are best classified as res nullius, appropriable by any persons, physical or legal, public or private, as long as they commit to certain requirements as to their profits, which culminates in a reasonable proposal of regulation for mining, which is both feasible and beneficial to mankind and the environment.

La exploración de los recursos minerales terrestres ha sido fuente de beneficios económicos, perjuicios ambientales y costos humanos. Nuevas tecnologías, sin embargo, están promoviendo la minería espacial con el potencial de, simultáneamente, maximizar los beneficios de esa actividad económica y reducir los daños socio-ambientales. Con esta perspectiva, el presente estudio examina dos implicaciones, en el ámbito jurídico, de esa innovación tecnológica: la naturaleza jurídica y la titularidad de los recursos naturales espaciales. Con los objetivos de reconocer al sujeto de derecho más plausible —según criterios jurídicos, lógicos y éticos— para obtener la titularidad del derecho de propiedad sobre minerales espaciales y de proponer el tratamiento más adecuado en relación a sus lucros, el abordaje adoptado pretende concatenar las explotaciones mineras terrestre y espacial sobre la base de la perspectiva de continuidad renovada. Para alcanzar esa proposición teórica, fueron analizados, previamente, los impactos humanos y ambientales de la minería terrestre; las viabilidades de utilización y de exploración de los minerales espaciales, así como las ventajas y desventajas de la minería espacial. Asimismo, se estudiaron los posicionamientos político-normativos —internacionales y locales—, así como los posicionamientos académicodoctrinarios — egacionistas, expansionistas y analogistas— acerca de ese derecho de propiedad. Se concluye que los minerales espaciales son mejor clasificados como res nullius, apropiables por cualquier persona, física o jurídica, pública o privada, siempre que se comprometan con determinados requisitos en cuanto a sus lucros, lo que culmina en una razonable propuesta de regulación para la minería espacial que es, simultáneamente, ejecutable y beneficiosa para la humanidad y el medio ambiente.
Space Ores: Nobody’s Things for the Benefit of All
Keywords: Minería espacial; Recursos espaciale; Res nulliu; Derecho espacial; Nuevo espacio; Nuevas tecnologías; https://purl.org/pe-repo/ocde/ford#5.05.00